2011
DOI: 10.1007/s00404-011-2103-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pelvic lymphadenectomy: experience of a Gynaecological Cancer Centre in the UK

Abstract: We are presenting the first reported series of exclusive laparoscopic transperitoneal lymphadenectomies from a Gynaecological Cancer Centre in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…However, gynecologic laparoscopic surgery carries a risk of complications. In this study, the incidence of minor complications was found to be 4.64%, which aligns with previous studies [3,4,13]. The rate of major complications was only 0.51%, lower than what has been reported by others [2,3].…”
Section: Results In the Context Of Published Literaturesupporting
confidence: 90%
See 2 more Smart Citations
“…However, gynecologic laparoscopic surgery carries a risk of complications. In this study, the incidence of minor complications was found to be 4.64%, which aligns with previous studies [3,4,13]. The rate of major complications was only 0.51%, lower than what has been reported by others [2,3].…”
Section: Results In the Context Of Published Literaturesupporting
confidence: 90%
“…Two additional patients experienced colonic injuries during total hysterectomy. Common strategies for managing rectal injuries include laparotomic or laparoscopic colostomy, one-stage repair, low anterior resection, and partial rectal resection [4,[22][23][24]. To minimize the risk of injury during laparoscopic surgery, it is crucial to ensure that the separation of the intestine is performed as close to the uterus as possible.…”
Section: Results In the Context Of Published Literaturementioning
confidence: 99%
See 1 more Smart Citation